Hugh Brady biographical account - Brady, Hugh, 1768-1851.
Biographical account pertaining primarily to the participation of Hugh Brady and other members of the Brady family in the U.S. Continental Army and to the military careers of Hugh Brady and his brother, Samuel Brady, following the American Revolution. Other family members represented include their father, John Brady (1733-1779), and brothers, James Brady and John Brady (1761-1851). The account covers the period between 1750 and 1860 and includes diary entries describing the march of the U.S. Army 3rd Infantry Regiment to Fort Clark, Tex., in June 1860. Mentions several officers participating in the march including Benjamin Louis Eulalie de Bonneville, John Trevitt, and Andrew Bowman.
U.S. Army officer.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Bonneville, Benjamin Louis Eulalie de, -- 1796-1878.; Bowman, Andrew, -- Captain; Brady, James, -- 1758-1778.; Brady, John, -- 1733-1779.; Brady, John, -- 1761-1809.; Brady, Samuel, -- 1756-1795.; Trevitt, John, -- 1821-1893.; United States. -- Army; United States. -- Army. -- Infantry Regiment, 3rd.; United States. -- Continental Army; Fort Clark (Tex.); United States -- History -- Colonial period, ca. 1600-1775.; United States -- History -- Revolution, 1775-1783.; United States -- History -- 1783-1865.; Army officers